PENGARUH KONSENTRASI SENYAWA BELERANG TERHADAP TINGKAT SERANGAN PENYAKIT JAMUR AKAR PUTIH PADA STUM OKULASI MATA TIDUR TANAMAN KARET - Junaidi Junaidi; Zaida Fairuzah (Jurnal Agro Estate, 2018)
ABSTRACT White root disease (WRD) is a very harmful disease in rubber planting material preparation. The treatment method for infected budded stump has not been determined; therefore, the infected stump is usually directly eradicated through burning. This research aimed to understand the eﬀect of the sulfuric compound to WRD rate and budded stump growth in polybag nursery. The research was arranged based on Completely Randomized Design (CRD) non-factorial with chemical concentration treatment using four levels i.e. 0 g/l (control), 2 g/l, 4 g/l, 6 g/l, dan 8 g/l that was carried out at Sungei Putih Research Center Greenhouse in Galang, Deli Serdang. The trial result indicated that the submersion of infected budded stump level two into sulfuric solution up to the concentration of 8 g/l for 15 minutes did not decrease WRD rate. The shoots growth showed was not significantly diﬀerent than without submersion. The submersion method is seemed not proper to treat WRD on the budded stump since it only can be conducted once at the beginning of the stump planting into the polybag. Therefore, research on the eﬀect of sulfur for WRD treatment on the budded stump has to be carried out variously from the dosage as well as application method viewpoint.